ANALISIS YURIDIS PENEGAKAN HUKUM TINDAK PIDANA PEMALSUAN KARTU TANDA PENDUDUK UNTUK MEWUJUDKAN PERLINDUNGAN DAN KEPASTIAN HUKUM (STUDI PENELITIAN DI PENGADILAN NEGERI BATAM) - Firma Oktavianti; Idham Idham; Christiani Prasetyasari (Ensiklopedia of Journal, 2022)
Current technological developments not only have a positive impact in Indonesia, but also have a negative impact. Like someone who commits forgery because of technological sophistication, it is difficult to distinguish between genuine documents and fake documents. The most common counterfeiting is the forgery of Identity Cards. This study aims to discuss the legal arrangements for falsification of Identity Cards and implementation, factors of obstacles and solutions to law enforcement of the criminal act of counterfeiting Identity Cards. The method used in this study is empirical normative. Sources of data in this study using literature, field and interview methods, as well as secondary data and primary data. Data analysis used qualitative analysis. The results showed that Article 263 of the Criminal Code regulates letter falsification. The panel of judges at the Batam District Court issued a decision on the criminal act of counterfeiting Identity Cards in accordance with article 263 of the Criminal Code. One of the obstacles is the number of unscrupulous civil servants who deviate from this identity making. The implementation of this case is that the Batam District Court is right in implementing law enforcement sanctions against the criminal act of counterfeiting Identity Cards. The Batam District Court needs to increase cooperation with related institutions by holding legal counseling for the public who are not aware of the law in order to minimize the occurrence of criminal acts.